Library Automation in Ghana: A Case Study of the Ghana Book Trust Children's Library - Akutsa, E. (University of Ghana, 2002)
Library automation bas been tagged the tool of the era. a medium by which the uncontrollable increase in Information could be managed and made easily accessible to the numerous users whose information needs are diverse. The acceptance of library automation has not wished away the great financial responsibilities that weigh heavily on many libraries especially in the developing countries, which has either delayed the automation process or prevented them from carrying out this important project. The GBT Children's library had financial support from an international aid agency, Ford Foundation and Ghana Book Trust, its parent organization in carrying out its computerization program ,that has also led to the expanded library service of IT education and enhancement of information resources and delivery. There is much awareness among the clients of the library to make use of these services but this expectation has not been met due to low staff strength and non availability of formal structures such as orientation of new members and IT course outline. There is also the need to put In place an IT policy for the maintenance and development of the system. The research looked at the factors that favored automation and it revealed that factors such as expert advice, financial aid from Ford Foundation and GBT Children', Library staff support led to the successful planning, implementation and maintenance of the automation project.
MA. Library Studies
Keywords: Library; Automation; Ghana; Children's Library; Ghana Book Trust